Inverse dynamics, joint reaction forces and loading in the musculoskeletal system: guidelines for correct mechanical terms and recommendations for accurate reporting of results - Baltzopoulos, V. (Sports Biomechanics, 2021)
Inverse Dynamics is routinely used in biomechanics for the estimation of loading in the musculoskeletal system but there are problems with the terms and definitions and even official recommendations introduce artificial and incorrect mechanical constructs to justify arbitrary and inappropriate terms. These terminology problems lead to further confusion and misinterpretations rather than to standardisation of mechanically correct nomenclature and accurate interpretation of joint loading. The perspective in this paper exposes some of the flawed foundational premises of these constructs and makes recommendations for accurate reporting of inverse dynamics outcomes and musculoskeletal loading. The inverse dynamics approach is based on free body diagrams that include the actual forces as applied ("Actual Forces" approach) or the replacement of actual forces with an equivalent resultant force and moment ("Resultant Moments" approach). Irrespective of the approach used to model the muscle and other forces, the inverse dynamics outputs always include the joint reaction forces representing the interactions with adjacent segments. The different terms suggested to distinguish the calculated joint reaction forces from the two approaches such as "net joint force", "resultant force", "intersegmental force" and "bone-on-bone force" are inappropriate, misleading and confusing. It is recommended to refer to joint reaction forces as Total or Partial when using an Actual Forces or a Resultant Moments approach, respectively.